A new floating inductor circuit using differential voltage current conveyors - Sedef, H; Acar, C (FACHVERLAG SCHIELE SCHON, 2000)
A new floating inductor circuit is proposed using two differential voltage current conveyors and a minimum number of passive elements. Since passive elements are all grounded, this circuit is suitable for fully integrated circuit design. Moreover it does not require any element matching condition. It has a good sensitivity performance due to tracking errors. The proposed inductor circuit can be controlled through with grounded resistors.
Keywords: Engineering